Experimental Test Of Indonesian Wood Joint Lateral Resistance With Bolt As Fasteners Versus Yield Limit Equations Of SNI 7973-2013 - Widojoko L; Surjokusumo S; Pranata Y A (International Conference on Engineering and Technology Development (ICETD), 2017)
The use of bolt fasteners as a connecting device has been used for a long time. Calculation of lateral resistance capacity used in Indonesia that is SNI 7973-2013 method is adopt American standard that is NDS 2012. Due to climate and weather difference since its growth, humidity factor and openness to sunshine and rain hence the nature of wood in Indonesia is different from wood in America. This study aims to examine the accuracy of the equation of lateral resistance capacity in the standard for timber in Indonesia.The results show that the comparison between the experimental results and the result of calculation by the method of SNI 7973-2013 is 92.7%, means that the method of SNI 7973-2013 is suited to the fastened joints of bolts for Indonesian wood